2022
DOI: 10.3390/s22155571
|View full text |Cite
|
Sign up to set email alerts
|

An Underwater Acoustic Network Positioning Method Based on Spatial-Temporal Self-Calibration

Abstract: The emergence of underwater acoustic networks has greatly improved the potential capabilities of marine environment detection. In underwater acoustic network applications, node location is a basic and important task, and node location information is the guarantee for the completion of various underwater tasks. Most of the current underwater positioning models do not consider the influence of the uneven underwater medium or the uncertainty of the position of the network beacon modem, which will reduce the accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…In view of the reality of the equal weight random model, Liu et al [3] considered the influence of the height angle correlation error on the positioning result, and established a weighting function considering the height angle of the sound ray; Xu et al [4] Considering that the observation environment of adjacent epochs is basically the same, and the sound velocity ranging error should not change much, drawing on the GNSS difference idea, the underwater differential positioning method is proposed for the underwater acoustic ranging delay observation measurement, which weakens the influence of the ranging system error; Yang et al [5] proposed a method for underwater static target localization without measuring the velocity profile of sound. In order to eliminate the weakening error; Lekkas [ 6] uses statistical testing methods to test the mass distribution of observations, improve the quality of observations, and improve the positioning results; Chen et al [7] a sample search method, which first searches for the vertical component of the best offset parameter and fixes it, and then solves the horizontal component of the offset parameter as the parameter to be estimated together with the coordinate parameter, which can significantly improve the solution effect; Considering the influence of coarseness, Shuang Zhao et al [8] used the weighted iteration of IGG3 to estimate on the basis of the difference algorithm; Mingzhen Xin [9] adopts a more general non-differential positioning model, combined with constant gradient sound line tracking, and proposes a complete set of sound line tracking and positioning calculation process; Anmin Zeng et al [10] systematically analyzed the positioning efficiency of underwater geodetic reference points in circular navigation mode, and found that although the differential positioning model in circular navigation mode weakens the influence of ranging system error, it also reduces the geometric observation intensity of the design matrix; Ma Yueyuan et al [11] proposed a symmetric epoch differential positioning model based on the premise that the system error parameters caused by sound velocity changes have certain periodicity.At present, the research on underwater positioning algorithm is mostly aimed at the non-differential positioning solution model, and the influence of systematic error is still the difficulty of high-precision positioning of underwater static targets.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the reality of the equal weight random model, Liu et al [3] considered the influence of the height angle correlation error on the positioning result, and established a weighting function considering the height angle of the sound ray; Xu et al [4] Considering that the observation environment of adjacent epochs is basically the same, and the sound velocity ranging error should not change much, drawing on the GNSS difference idea, the underwater differential positioning method is proposed for the underwater acoustic ranging delay observation measurement, which weakens the influence of the ranging system error; Yang et al [5] proposed a method for underwater static target localization without measuring the velocity profile of sound. In order to eliminate the weakening error; Lekkas [ 6] uses statistical testing methods to test the mass distribution of observations, improve the quality of observations, and improve the positioning results; Chen et al [7] a sample search method, which first searches for the vertical component of the best offset parameter and fixes it, and then solves the horizontal component of the offset parameter as the parameter to be estimated together with the coordinate parameter, which can significantly improve the solution effect; Considering the influence of coarseness, Shuang Zhao et al [8] used the weighted iteration of IGG3 to estimate on the basis of the difference algorithm; Mingzhen Xin [9] adopts a more general non-differential positioning model, combined with constant gradient sound line tracking, and proposes a complete set of sound line tracking and positioning calculation process; Anmin Zeng et al [10] systematically analyzed the positioning efficiency of underwater geodetic reference points in circular navigation mode, and found that although the differential positioning model in circular navigation mode weakens the influence of ranging system error, it also reduces the geometric observation intensity of the design matrix; Ma Yueyuan et al [11] proposed a symmetric epoch differential positioning model based on the premise that the system error parameters caused by sound velocity changes have certain periodicity.At present, the research on underwater positioning algorithm is mostly aimed at the non-differential positioning solution model, and the influence of systematic error is still the difficulty of high-precision positioning of underwater static targets.…”
Section: Introductionmentioning
confidence: 99%
“…Floating LBLs have been widely used in underwater positioning practice due to their ability to accurately obtain global positioning system (GPS) information through buoys [11]. However, the positions of the buoys are susceptible to the water current, making them unsuitable for providing stable positioning services to underwater targets for extended periods.…”
Section: Introductionmentioning
confidence: 99%